Auxiliary ligand-assisted structural diversities of two coordination polymers with 2-hydroxyquinoline-4-carboxylic acid - Mal, Dasarath
The solvothermal reactions of Cd(NO3)(2).6H(2)O with 2-hydroxyquinoline-4-carboxylic acid (H(2)hqc) and 4,4'-bipyridine (bpy) or trans-1,2-bi(4-pyridyl)ethylene (bpe) afforded two coordination polymers [Cd(H-hcic)(2)(bpy)(H2O)(2)](n) (1) and [Cd(H-hqc)(2)(bPe)(0.5)](n) (2), respectively. The bipyridine based auxiliary ligands such as bpy and bpe were selected in order to analyze the effect of the length of auxiliary ligands on the formation of coordination polymers. Compounds 1 and 2 were characterized by elemental analysis, IR, and single crystal X-ray diffraction. Compound 1 shows a one-dimensional (1D) chain structure with linear topology while compound 2 shows 2D network with 3,6-c binodal net, having point symbol {3(2).4}(3(4). 4(3).5(2).6(5).7} and vertex symbol [33.6(2)][3.3.3.3.6(2).6(2).6(2).6(2).6(2).*.*.*.*.*]. The results show that the spacer lengths of N-donor ligands do effect the topological structures of cadmium(II) coordination polymers. (C) 2013 Elsevier B.V. All rights reserved.